2020
DOI: 10.1101/2020.08.21.261412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

5’XP sRNA-seq: Efficient Identification of Transcripts With and Without 5’ Phosphorylation Reveals Evolutionary Conserved Small RNA

Abstract: Small RNA (sRNA) sequencing has been critical for our understanding of the transcriptional regulation in most biological processes. Nonetheless, the varying biochemical properties of sRNA, such as 5' nucleotide modifications, make many sRNA subspecies incompatible with common protocols for sRNA sequencing. Here we describe 5XP-seq that outlines a novel strategy on how to overcome this limitation. By specifically tagging 5'-phosphorylated sRNA (5'P sRNA), that enriches miRNA and piRNA, we successfully discrimin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…For the Peak and Peak rRNA fragments we have previously observed similar fragments in human sperm (8), and similar fragments located to the 5' ends of the 5.8S and 28S subunits in fruit fly embryos (44). This is also true for the 3' fragments of the 28S subunit (Peak 4), even though we never have observed such expression levels as we see in the HeLa cells.…”
Section: Seqpac Example 2: Novel Rrna-derived Srna Affected By Anticasupporting
confidence: 82%
See 4 more Smart Citations
“…For the Peak and Peak rRNA fragments we have previously observed similar fragments in human sperm (8), and similar fragments located to the 5' ends of the 5.8S and 28S subunits in fruit fly embryos (44). This is also true for the 3' fragments of the 28S subunit (Peak 4), even though we never have observed such expression levels as we see in the HeLa cells.…”
Section: Seqpac Example 2: Novel Rrna-derived Srna Affected By Anticasupporting
confidence: 82%
“…Blasting this sequence showed that it was identical to the complete 2S rRNA subunit. This was expected since Kang et al did not to report of any method that depletes 2S rRNA prior to library construction, which is commonly done in fruit fly experiments (43, 44). The human proportion of the dataset was instead enriched with miRNA with the expected size of 22 nt (Figure 4B).…”
Section: Results and Descriptionmentioning
confidence: 99%
See 3 more Smart Citations